Designing a Multiple-choice Vocabulary Test for Office Administration Students - Demetria Tri Adri Suyati (Journal of English Language Teaching and English Linguistics, 2025)
This study aims to design a vocabulary test for College Students of Office Administration Study Program at Akademi Sekretari dan Manajemen Indonesia Desanta. The research design of this study was Reaseach and Development (R&D) and it applied ADDIE Model. The steps of the model are Analysis, Design, Develop, Implementation and Evaluation. The type of data of this research was quantitative data. The research instrument was multiple-choice vocabulary test. The findings showed that the multiple-choice vocabulary test was reliable and valid and able to use as a well-designed vocabulary test to measure the vocabulary mastery of the students. It can be seen from the discrimination power, difficulty level, validity, and reliability of the product obtained from the score of the students’ answers.